Refleks Fonem Proto Melayu-Polinesia Pada Bahasa Biak dan Bahasa Waropen. Reflex of Malayu-Polynesian Proto Phonemes in Biakic and Woropen Languages - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
This thesis examines the Reflexes of Malayo-Polynesian Proto Phoneme in Biakic (BB) and Waropen (BW) languages, two of several languages in West Irian Jaya, belonging to the Austronesian (AN) language family. The method used in the research is a Top-Down Reconstruction Method, while the data were gathered through interview and recording technique. Then, the data were cultivated and analyzed separately in two categories between BB and BW, using a comparative technique. The comparative technique was employed to observe the proto phonemes which have reflexes or mirroring, and to observe the innovations in these two languages. From the data analysis, the researcher finds out that there are reflexes of PMP either in Biakic language or Waropen language. The reflexs occur independently but some, though not many, occur simultaneously. In addition, the results also show that there are phonemic innovations in these two languages. The phonemic shared innovations that occured common to these two languages are phonological innovations, which shift, merger, and split. This research did not find any correspondence between these two languages, and there are no adopted elements from Indonesian language, or Malay as well from foreign languages. Apart from this research, this study still needs a further research especially into these two languages or into the languages existing in Geelvink Bay which belong to the sub-family of AN. It is also hoped that fiiirther researches will be focused on the reconstruction of the proto languages existing in Geelvink Bay, and on the compilation of Eastern Malayo-Polynesian proto dictionary especially those existing in South Halmahera and Irian Jaya.